Collapse of layer dimerization in the photo-induced hidden state of 1T-TaS2 - Quirin Stahl (Nature Portfolio, 2020)
The microscopic understanding of photo-induced insulator-to-metal transition (IMT) in 1T-TaS2 remains elusive. Here, Stahl et al. identify the collapse of interlayer molecular orbital dimers during a collective electronic phase transition as a key mechanism for the IMT in 1T-TaS2.